Impact of Increased Long-Term Care Insurance Payments on Employment and Wages in Formal Long-Term Care - Ayako Kondo (Institute of Labor Economics (IZA), 2019)
This paper examines the effect of raising Long-term Care Insurance (LTCI) payments on employment and wages of workers in the long-term care (LTC) industry. Specifically, I use the change in the regional premium in 2012 as an exogenous shock to the insurance fee schedule: the change in the unit price of LTCI service ranges from a decrease of 2.8% to an increase of 4.2%. I find no increase in the number of employees in the establishments, registered under the LTCI scheme, in municipalities where the regional premium increased. The earnings and working hours of LTC workers did not increase, either.
Keywords: I11; J30; J48; 330; long-term care insurance; care workers